World War Z - Forster, Marc, 1969-; Pitt, Brad, 1963-; Enos, Mireille, 1975-; Kertesz, Daniella; Beltrami, Marco; Brooks, Max. (Hollywood, Calif. : Paramount, 2013)
After narrowly escaping zombie hordes in Philadelphia and finding refuge with his family on an aircraft carrier in the Atlantic ocean, ex-United Nations investigator Gerry Lane travels the globe in search of a cure to save what is left of humanity.
Originally released as a motion picture in 2013.
Based on the novel by Max Brooks.
Dolby digital 5.1, wide screen 1.85:1.
Camera, Ben Seresin ; production designer, Nigel Phelps ; editors, Roger Barton, Matt Chesse ; music, Marco Beltrami.
Brad Pitt, Mireille Enos, Daniella Kertesz, James Badge Dale, Ludi Boeken.
MPAA rating: PG-13.
Keywords: Brooks, Max -- Film adaptations; Zombies -- Drama; Epidemics -- Drama; Zombie films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Thriller films; Based on the book; Feature films; Horror films; Science fiction films